Gerakan Dakwah pada Organisasi Al-Washliyah - Maratua Hasonangan Harahap; Suparto Suparto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The Al-Washliyah organization is an Islamic organization that has an important role in preaching and developing Islamic teachings in Indonesia. The da'wah movement carried out by Al-Washliyah carries a vision and mission to spread Islamic teachings with a moderate, inclusive approach and prioritizing noble morals. The Al-Washliyah da'wah movement does not only focus on spreading religious knowledge, but also on strengthening social and community education, especially in introducing Islam that rahmatan lil-'alamin (mercy for all nature). This movement can be seen in various aspects, starting from teaching at the madrasa level, developing the community through social activities, to involving members in religious organizations. Al-Washliyah also plays a role in encouraging society to maintain harmony between people, respect differences, and strengthen the ties of Muslim brotherhood. In carrying out da'wah, Al-Washliyah adopts an approach that combines an understanding of religious knowledge based on the Al-Qur'an and Hadith, as well as the application of social values that are relevant to the needs of society. Da'wah Al-Washliyah focuses on forming good character, not only from a religious perspective but also from a social and moral perspective. Through a network of religious studies, seminars and other social activities, Al-Washliyah has succeeded in building a more organized and competitive community of believers. Thus, the da'wah movement carried out by Al-Washliyah is not just about spreading knowledge, but also creating more positive social change in people's lives.